1999
DOI: 10.1016/s1098-7339(99)90159-1
|View full text |Cite
|
Sign up to set email alerts
|

A survey of exposure to regional anesthesia techniques in American anesthesia residency training programs

Abstract: Most CA-3 residents are confident in performing lumbar epidural and spinal anesthesia. However, many are not confident in performing the blocks with which they have the least exposure. Changes need to be made in the training processes so that residents can graduate with enough confidence to continue selecting less familiar blocks in postgraduate practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 4 publications
1
25
0
1
Order By: Relevance
“…At least 50% of residents reported little to no experience with blockade of the brachial plexus, sciatic, and femoral nerves. 1 Experience with 40 peripheral nerve blocks is currently required by the Accreditation Council of Graduate Medical Education (ACGME). 2 The requirement does not specify a minimum number for individual peripheral nerve blocks, and as such, graduating residents may not have developed adequate expertise in any one block.…”
mentioning
confidence: 99%
“…At least 50% of residents reported little to no experience with blockade of the brachial plexus, sciatic, and femoral nerves. 1 Experience with 40 peripheral nerve blocks is currently required by the Accreditation Council of Graduate Medical Education (ACGME). 2 The requirement does not specify a minimum number for individual peripheral nerve blocks, and as such, graduating residents may not have developed adequate expertise in any one block.…”
mentioning
confidence: 99%
“…8 Peripheral nerve blocks are an essential component of multimodal analgesia techniques to provide safe and effective postoperative pain management with minimal side effects. 9 Surveys of residency programs have established that the number of peripheral nerve blocks performed during residency is indeed limited, 10,11 and these residents lack confidence in their ability to perform such blocks. 12 Sloan et al 13 have demonstrated that a short course in pain management given to medical students improved their knowledge and attitudes about opioid analgesic use in cancer patients.…”
mentioning
confidence: 99%
“…26 Surveys among practicing anesthesiologists have shown that adequate training poses a major driving factor in the application of regional anesthesia. 39 Neuraxial techniques are commonly performed with a high level of confidence, in part because these procedures are thoroughly covered in residency programs and technically easy to perform. [40][41][42] However, neuraxial techniques are not a viable option for surgeries of the upper extremity, and even for the lower extremity, some authors have reported advantages with the use of PNBs.…”
Section: Discussionmentioning
confidence: 99%